Association of two independent functional risk haplotypes in TNIP1 with systemic lupus erythematosus (2012)
Objective Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by autoantibody production and altered type I interferon expression. Genetic surveys and genome-wide association studies have identified >30 SLE susceptibility genes. One of these genes, TNIP1, encodes the ABIN1 protein. ABIN1 functions in the immune system by restricting NF-?B signaling. The present study was undertaken to investigate the genetic factors that influence association with SLE in genes that regulate the NF-?B pathway. Methods We analyzed a dense set of genetic markers spanning TNIP1 and TAX1BP1, as well as the TNIP1 homolog TNIP2, in case-control populations of diverse ethnic origins. TNIP1, TNIP2, and TAX1BP1 were fine-mapped in a total of 8,372 SLE cases and 7,492 healthy controls from European-ancestry, African American, Hispanic, East Asian, and African American Gullah populations. Levels of TNIP1 messenger RNA (mRNA) and ABIN1 protein in Epstein-Barr virus-transformed human B cell lines were analyzed by quantitative reverse transcription-polymerase chain reaction and Western blotting, respectively. Results We found significant associations between SLE and genetic variants within TNIP1, but not in TNIP2 or TAX1BP1. After resequencing and imputation, we identified 2 independent risk haplotypes within TNIP1 in individuals of European ancestry that were also present in African American and Hispanic populations. Levels of TNIP1 mRNA and ABIN1 protein were reduced among subjects with these haplotypes, suggesting that they harbor hypomorphic functional variants that influence susceptibility to SLE by restricting ABIN1 expression. Conclusion Our results confirm the association signals between SLE and TNIP1 variants in multiple populations and provide new insight into the mechanism by which TNIP1 variants may contribute to SLE pathogenesis. Copyright © 2012 by the American College of Rheumatology.